The Times They are A-Changin' - Michael Rosholm; Kirk Scott; Leif Husted (Institute for the Study of Labor (IZA), 2001)
This article compares and contrasts male immigrant labor market experiences in Sweden and Denmark during the period 1985 - 1995. Using register-based panel data sets from Sweden and Denmark, a picture of the employment assimilation process of immigrants from Norway, Poland, Turkey, and Iran is brought forth. The comparative approach shows that immigrants in Sweden and Denmark experienced similar declines in employment prospects between 1985 and 1995 despite quite different developments of aggregate labor market conditions. The explanation offered here is that the changing organizational structure – towards more flexible work organization - has resulted in a decrease in the attractiveness of immigrant employees due to the increasing importance of country-specific skills and informal human capital.
Keywords: J61; J71; L23; O30; 330; Immigrants; employment assimilation; organizational change; Einwanderung; Internationale Arbeitsmobilität; Ausländische Arbeitskräfte; Arbeitslosigkeit; Arbeitsorganisation; Reorganisation; Schätzung; Dänemark; Schweden